2020
DOI: 10.1080/01609513.2020.1836548
|View full text |Cite
|
Sign up to set email alerts
|

PLEASE be with me: benefits of a peer-led supervision group for early career social work educators

Abstract: Junior social work faculty members face numerous challenges in adapting to their roles and preparing for continued work in academia. Many of these challenges center around the tasks of teaching and advising. Peer-led, mutual support groups offer an accessible and effective approach to facilitating growth. Such groups offer support that addresses several common challenges facing new faculty, primarily by helping to combat isolation, and facilitate group attachment. The article draws from literature on mutual ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 31 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…This corroborates with the stress buffer model (Olstad et al, 2001), in that social support buffers against the negative impact of stress. The positive impact of social support networks can include increasing confidence; overcome feelings of isolation, as well as assisting an individual to express their emotions and challenge any denial or negative beliefs in a positive and safe way (Wenocur et al, 2020). Various participants revealed that although they come from large families and have good friendship groups, they did often feel hesitant to confide in such individuals to discuss their emotional difficulties.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…This corroborates with the stress buffer model (Olstad et al, 2001), in that social support buffers against the negative impact of stress. The positive impact of social support networks can include increasing confidence; overcome feelings of isolation, as well as assisting an individual to express their emotions and challenge any denial or negative beliefs in a positive and safe way (Wenocur et al, 2020). Various participants revealed that although they come from large families and have good friendship groups, they did often feel hesitant to confide in such individuals to discuss their emotional difficulties.…”
Section: Analysis and Discussionmentioning
confidence: 99%